Rethinking Strategy for SMEE Support in the Light of the Entrepreneurial Ecosystem - Miroljub Hadzic; Petar Pavlovic (Ital Publication, 2019)
Serbia has started transition in 2000. Although it experienced fast growth prior to the global economic crisis, critical number of SMEs was not created to achieve a sustainable development of entrepreneurial sector. During the crisis period SMEs faced with development limits, especially shops and micro companies. In the period 2009-2014 Serbian economy had zero rate of growth, the business climate was generally somewhat deteriorated and support to SMEE weakened by Government, local level of governance and financial institutions. There are positive signs of economic recovery of Serbia during 2015 and 2016. The market reforms got momentum in some important areas. The Government successfully put under control huge budget deficit and public debt. The inflation rate became for the first time low, similar to the European level. The Strategy for support SME, entrepreneurship and competitiveness in the period 2015-2020 was enacted at the end of 2014. Its importance became critical considering weaknesses of entrepreneurial sector, bottlenecks and limits of existing governmental measures for SMEE support. The point is to highlight those from the point of view of development the entrepreneurial ecosystem, as a new conceptual framework designed to foster economic development via entrepreneurship, innovation and small business growth.